Design and Development of the HelpDesk Application for the Faculty of Information Technology, Tarumanagara University (FTI UNTAR) using the Agile Scrum Methodology - Alvin Nicolas Gunadi; Dedi Trisnawarman; Manatap Dolok Lauro (Sean Institute, 2024)
At the Faculty of Information Technology, there is currently no structured division of tasks, so the task management process is carried out manually through the WhatsApp application. This causes difficulties in monitoring and completing tasks efficiently, and has the potential to cause confusion and delays. Therefore, a system is needed that can manage tasks and tickets effectively. The general theory discussed in this text covers the basic concepts and principles underlying the research topic, including relevant theories in the chosen field of study as well as methodological approaches. Websites play an important role in presenting interactive web pages for various purposes such as information dissemination, online transactions, communication, entertainment, and education. Websites can be static or dynamic, built using technologies such as HTML, CSS, and JavaScript. Systematic helpdesk management helps in resolving user issues efficiently through automated processes and structured communication channels. The Agile Scrum method is applied for agile development in designing a web-based ticketing helpdesk system, focusing on incremental delivery of value through user stories, product backlog management, sprints, and user acceptance testing. Use case scenarios, activity diagrams, and sequence diagrams are used for clear system visualization and documentation, ensuring efficient system development to meet user needs.